The C-Terminus of Epstein-Barr Virus BRRF2 Is Required for its Proper Localization and Efficient Virus Production - Watanabe, Takahiro; Sakaida, Keiya; Yoshida, Masahiro; Masud, H. M. Abdullah Al; Sato, Yoshitaka; Goshima, Fumi; Kimura, Hiroshi; Murata, Takayuki (Frontiers in Microbiology, 2017)
Epstein-Barr virus (EBV) is a human gammaherpesvirus associated with several malignancies. We reported previously that an EBV lytic gene product BRRF2 is involved in the maturation of progeny virus. To analyze the domain(s) needed for efficient production of progeny, we prepared a series of deletion mutants and found two functional domains in the N- and C-terminal regions by complementation assays. Immunofluorescence analyses revealed that BRRF2 lacking the C-terminal region demonstrated aberrant localization in both the nucleus and cytoplasm, whereas wild-type BRRF2 was localized predominantly in the cytoplasm. We also confirmed that wild-type BRRF2 co-localized with Rab5, an endosomal marker, at least partly. Additionally, serine 511 of BRRF2 was phosphorylated during lytic infection; however, a mutant in which the serine was substituted with alanine still augmented the yield as efficiently as did wild-type BRRF2. These results showed that the C-terminal region of BRRF2 is involved in the predominant localization of BRRF2 to the cytoplasm and in the efficient production of infectious virus.